The ratchet effect in a two lag setting and the mitigating influence of yardstick competition - Cord Brockmann (Universität Augsburg, Institut für Volkswirtschaftslehre, 2007)
In order to increase efficiency in the provision of power distribution networks, the German regulator Bundesnetzagentur plans to implement revenue cap regulation together with yardstick competition. Revenue cap regulation could bear the ratchet effect: cost minimization need not to be optimal for the operator who anticipates that his revenue cap will become adjusted according to his cost performance. The regulator could extract all the rent by lowering an operator?s revenue cap to the level of costs he revealed to be possible for him to reach. The ratchet effect could be mitigated by yardstick competition at which the level of revenues that is allowed to one operator is tied to the performance of others that are comparable to him. One will only be allowed to accumulate revenues that recover the least cost level that has been adopted within the group of comparable decision makers. In a setting of two sequential regulatory lags, this paper examines the occurence of the ratchet effect and the mitigating influence that yardstick competition has on it.
urn:nbn:de:bvb:384-opus4-711440
Keywords: L51; 330; ratchet effect; yardstick competition; regulation